2018
DOI: 10.1021/acs.jmedchem.8b00143
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Marinoquinolines as Potent and Fast-Acting Plasmodium falciparum Inhibitors with in Vivo Activity

Abstract: We report the discovery of marinoquinoline (3 H-pyrrolo[2,3- c]quinoline) derivatives as new chemotypes with antiplasmodial activity. We evaluated their inhibitory activities against P. falciparum and conducted a structure-activity relationship study, focusing on improving their potency and maintaining low cytotoxicity. Next, we devised quantitative structure-activity relationship (QSAR) models, which we prospectively validated, to discover new analogues with enhanced potency. The most potent compound, 50 (IC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 65 publications
1
37
0
2
Order By: Relevance
“…The QSAR can provide predictive models based on mathematical and statistical relations that can be used to optimize the design of known types of chemical drugs to achieve an improved activity. 21,22 However, there are still very few studies focused on the design of nanomedicines with the assistance of QSAR or other CADD techniques. 23 Here, we explored the potential of developing predictive computer models for a series of water-soluble fullerene derivatives acting as inhibitors of NSCLC cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…The QSAR can provide predictive models based on mathematical and statistical relations that can be used to optimize the design of known types of chemical drugs to achieve an improved activity. 21,22 However, there are still very few studies focused on the design of nanomedicines with the assistance of QSAR or other CADD techniques. 23 Here, we explored the potential of developing predictive computer models for a series of water-soluble fullerene derivatives acting as inhibitors of NSCLC cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…The pyrrolo[2,3‐c]quinoline 103 with IC 50 of 39 and 41 nM against CQS 3D7 and multidrug‐resistant K1 strains respectively was intoxic toward HepG2 cells (EC 50 : >250 μM), and SI was more than 6400 . IC 50 values of compound 103 (28‐50 nM) against asynchronous, rings, trophozoites, and schizont were equivalent to the values for the ring stages, suggesting that this compound was a potent inhibitor of all erythrocytic forms of P falciparum .…”
Section: Quinoline Hybridized With Novel Antimalarial Pharmacophores mentioning
confidence: 95%
“…All mice survived after oral treatment with a 1000 mg/kg dose, demonstrating its excellent safety profile. On the basis of the above research results, compound 103 could be acted as a lead compound for the discovery of new antimalarial agents …”
Section: Quinoline Hybridized With Novel Antimalarial Pharmacophores mentioning
confidence: 97%
“…Aiming at further exploring the potential of marinoquinolines as antimalarial compounds, in 2018, Correia, Guido and co‐workers reported the discovery of unnatural analogues as new leading candidates for antimalarial drug development [46] . Several MQ analogues were synthesized in a very flexible strategy and they were then tested for their inhibitory activity against P. falciparum involving SAR and QSAR analysis as well as in vitro and in vivo studies.…”
Section: Total Synthesis Of Natural and Unnatural Marinoquinolines And Biological Studies (2006 To 2020)mentioning
confidence: 99%
“…The complementary CoMFA analysis also showed that bulky and electropositive substituents at the 4‐phenyl position of the marinoquinoline core increases the potency. Using the insights provided by the QSAR studies, the new derivatives 118 – 120 (Table 4, entries 4–6) were synthetized and evaluated for their biological activity [46] …”
Section: Total Synthesis Of Natural and Unnatural Marinoquinolines And Biological Studies (2006 To 2020)mentioning
confidence: 99%